Caregiving can be costly: A qualitative study of barriers and facilitators to conducting kangaroo mother care in a US tertiary hospital neonatal intensive care unit - Todd P. Lewis; Kathryn G. Andrews; Elyse Shenberger; Theresa S. Betancourt; Günther Fink; Sunita Pereira; Margaret McConnell (BMC, 2019)
Abstract Background Preterm birth is a leading cause of morbidity and mortality in children under five and often requires a newborn to have an extended stay in a neonatal intensive care unit (NICU). Maternal engagement, such as visiting the NICU to provide kangaroo mother care (KMC), can improve outcomes for preterm infants but requires significant investment of time and resources. This study sought to understand barriers and facilitators to provision of KMC in the NICU. Methods We conducted semi-structured in-depth interviews with mothers of preterm infants (N = 20) at a large academic medical center in Massachusetts. A series of open-ended interview questions were designed to elicit all aspects of mothers' experiences and to understand how these experiences influence provision of KMC. All interviews were recorded and transcribed verbatim. We conducted an inductive thematic analysis to identify themes in the data with a focus on the barriers and facilitators of KMC provision in the NICU. Results Findings show that engaging in KMC is heavily influenced by the mental, emotional, and physical effects of preterm birth on the birth mother, such as stress around preterm birth and difficulty recovering from birth. These challenges are compounded by structural barriers such as costly accommodations, unreliable transportation, lack of child care, and inadequate maternity leave policies that limit the frequency and duration of KMC and parental ability to provide care. Conclusions A complex array of mental, emotional, physical, and structural factors determine a mother's ability to visit the NICU and provide kangaroo mother care. Providing social supports, such as improved maternity leave policies and reliable hospital access through child care, accommodation, and transportation services, may address the structural barriers that inhibit KMC, reduce burdensome costs, and improve the health of mothers and their preterm infants.